Deflagration Waves Out of Hot Spots - Partom, Yehuda (European Journal of Applied Sciences, 2022)
It is widely accepted that shock initiation and detonation of heterogeneous explosives come about by a two-step process known as ignition and growth. In the first step a shock, sweeping through an explosive cell (control volume), creates hot spots that become ignition sites. In the second step deflagration waves (or burn waves) propagate out of those hot spots and transform the reactant in the cell into reaction products. The macroscopic (or average) reaction rate of the reactant in the cell depends on the speed of those deflagration waves and on the average distance between neighboring hot spots. Here we simulate the propagation of deflagration waves out of hot spots on the mesoscale in axial symmetry using a 2D hydrocode, to which we add heat conduction and bulk reaction. The propagation speed of the deflagration waves may depend on both pressure and temperature. It depends on pressure for quasistatic loading near ambient temperature, and on temperature at high temperature levels resulting from shock loading. From the simulation we obtain deflagration (or burn) fronts emanating out of the hot spots. For intermediate shock levels the emanating fronts propagate as deflagration waves to consume the explosive between hot spots. For higher shock levels the deflagration waves interact with the sweeping shock to become detonation waves on the mesoscale. From the simulation results we extract average deflagration wave speeds.